Recurrent ovarian cancer: prolongation of the platinum-free interval with the use of a weekly treatment regimen of hycamtin (topotecan) - E. G. Novikova; I. A. Korneyeva; E. Yu. Moskovskaya (Опухоли женской репродуктивной системы, 2014)
The efficacy and safety of intravenous topotecan (hycamtin) given in a dose of 4 mg/m2 on days of 1, 8, 15 of a 28-day cycle of its therapy were evaluated in patients with recurrent ovarian cancer (OC).Preliminary analysis of the safety and toxicity of the topotecan regimen demonstrated no impact on quality of life, easiness-to-use, and possible outpatient use. Topotecan showed to be effective as second- and higher line therapy for recurrent OC to carry out a platinum reduction.